Analysis of the approach angle to medial orbitotomy that avoids accidental neurotrauma in the mesaticephalic dog skull utilizing 3D computer models and virtual surgical planning - Congiusta, Michael C.; Soukup, Jason W. (Frontiers in Veterinary Science, 2023)
This study was conducted to determine an approach angle to medial orbitotomy that avoids accidental neurotrauma in mesaticephalic dogs. Medical records of dogs with mesaticephalic skulls that presented to the veterinary medical teaching hospital for head computed tomography (CT) between September 2021 and February 2022 were reviewed. Descriptive data were queried and CT findings were analyzed. Dogs greater than 20kg and possessing a disease free orbitozygomaticomaxillary complex (OZMC) on at least one side of the skull were included in the study. Digital imaging and communications in medicine (DICOM) files of head CT studies were imported into medical modelling software and the safe approach angle for medial orbitotomy was determined using three-dimensional (3D) computer models and virtual surgical planning (VSP) principles. Angles were measured along the ventral orbital crest (VOC) from the rostral cranial fossa (RCF) to the rostral alar foramen (RAF). The safe approach angle at four points from rostral to caudal along the VOC was measured. Results at each location were reported as mean, median, 95% CI, interquartile ranges and distribution. Results were statistically different at each location and generally increased from rostral to caudal. The variance between subjects and differences between locations were large enough to suggest a standard safe approach angle in mesaticephalic dogs cannot be determined and should be measured for each patient. A standardized approach angle to medial orbitotomy is not possible in the mesaticephalic dog. Computer modeling and VSP principles should be implemented as part of the surgical planning process to accurately measure the safe approach angle along the VOC.